2001
DOI: 10.1590/s0100-879x2001000300004
|View full text |Cite
|
Sign up to set email alerts
|

ClC-5 chloride channel and kidney stones: what is the link?

Abstract: Nephrolithiasis is one of the most common diseases in the Western world. The disease manifests itself with intensive pain, sporadic infections, and, sometimes, renal failure. The symptoms are due to the appearance of urinary stones (calculi) which are formed mainly by calcium salts. These calcium salts precipitate in the renal papillae and/ or within the collecting ducts. Inherited forms of nephrolithiasis related to chromosome X (X-linked hypercalciuric nephrolithiasis or XLN) have been recently described. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Positional cloning revealed that this disease, as well as X-linked recessive nephrolithiasis, X-linked hypophosphatemic rickets, and idiopathic low-molecular weight proteinuria of Japanese children, are all the results of defects in the CLC-5 chloride channel (78 -81). The CLC family of chloride channels encompasses nine members, including CLC-Kb, involved in some cases of Bartter disease (see below) (82,83) and CLC-1, the muscle chloride channel, mutated in Thomsen myotonia (84). These channels are voltage-gated and outwardly rectifying, with a high selectivity for chloride.…”
Section: Renal Calcium Transportmentioning
confidence: 99%
“…Positional cloning revealed that this disease, as well as X-linked recessive nephrolithiasis, X-linked hypophosphatemic rickets, and idiopathic low-molecular weight proteinuria of Japanese children, are all the results of defects in the CLC-5 chloride channel (78 -81). The CLC family of chloride channels encompasses nine members, including CLC-Kb, involved in some cases of Bartter disease (see below) (82,83) and CLC-1, the muscle chloride channel, mutated in Thomsen myotonia (84). These channels are voltage-gated and outwardly rectifying, with a high selectivity for chloride.…”
Section: Renal Calcium Transportmentioning
confidence: 99%
“…Hence, although from the data it appears that the lower T-Ox, the higher the MA, it is in fact T-Ca that takes an intermediate position between T-Ox and MA, in agreement with the negative correlations (Table 2). Third, a primacy of CaPi solid formation may be deduced from additional disturbances: the pronounced element peaks of potassium and chloride among the energy spectrum associated with immature CaPi (Figure 2B-2) are -in the case of potassium -reminiscent of the transition of amorphous CaPi to hydroxyapatite in extra-renal calcifying tissues, a process normally under the control of an organic proteinaceous matrix (30), and -in the case of chloride -may reflect malregulated tubular acid-base status, which is increasingly under discussion as a possible factor in stone etiology (31). With regard to the transformation of CaPi to hydroxyapatite, the in vitro induction of nonphysiological urinary Ca excess at pH 6.0 reveals that urine can act as a Ca sink: when Ca and Pi ions become associated with binding sites of proteinaceous macromolecules (see C/U values )1, Figure 1) not only amorphous CaPi will form, but this phase simultaneously accelerates the incipient maturation to Ca-rich hydroxyapatite (containing up to 10 mol Ca per mol CaPi) rather than brushite (containing 1 mol Ca per mol CaPi).…”
Section: Caox or Capi -Which Crystal Comes First?mentioning
confidence: 99%
“…Regarding the metabolic environment in interstitium, bicarbonate enrichment of blood (Table 2) may hint towards leakage of basolateral cell membranes for this anion, mainly of distal tubular cells, owing to a genetic defect [55] or acquired insufficient ATPase-dependent H + generation. As mentioned above, clinically inapparent (intracellular) acidosis may be a so far neglected feature of IRCU, all the more as the elemental peaks of chloride and potassium (Figure 2, A-2-C-2) may - in the case of chloride - reflect malregulation of renal-tubular acid-base status, which is discussed as a possible factor in Ca stone etiology [57], and - in the case of potassium - is reminiscent of the transition of amorphous CaPi to HAP, a process that in calcifiying tissues is under the control of both cellular acid-base status [55] and matrix proteins [56]. In the light of present and other recent work the question "is ROS excess a primary event or secondary to interaction of renal epithelium with HAP [58]" deserves more conclusive addressing: 1) In IRCU HAP was found within the basolateral membrane of, and juxtapositioned outside, the thin part of loop of Henle [59,60], and alkalization of interstitium is pre-requisite for HAP formation [36]; 2) the inverse correlations of blood bicarbonate with insulin and BMI (APPENDIX, II (Figure 3), f and h), together with the observation that oxidatively modified metabolism in the form of a trend towards systemic alkaline tide (rise of blood bicarbonate and pH) coincides with a higher pressure to form stones (Table 2), are strong hints that ROS excess, extracellular bicarbonate accumulation and extratubular HAP development may be interrelated.…”
Section: Discussionmentioning
confidence: 99%